Omics‐based molecular analyses of adhesion by aquatic invertebrates. (16th February 2021) - Davey, Peter A.; Power, Anne Marie; Santos, Romana; Bertemes, Philip; Ladurner, Peter; Palmowski, Pawel; Clarke, Jessica; Flammang, Patrick; Lengerer, Birgit; Hennebert, Elise; Rothbächer, Ute; Pjeta, Robert; et al.
ABSTRACT: Many aquatic invertebrates are associated with surfaces, using adhesives to attach to the substratum for locomotion, prey capture, reproduction, building or defence. Their intriguing and sophisticated biological glues have been the focus of study for decades. In all but a couple of specific taxa, however, the precise mechanisms by which the bioadhesives stick to surfaces underwater and (in many cases) harden have proved to be elusive. Since the bulk components are known to be based on proteins in most organisms, the opportunities provided by advancing 'omics technologies have revolutionised bioadhesion research. Time‐consuming isolation and analysis of single molecules has been either replaced or augmented by the generation of massive data sets that describe the organism's translated genes and proteins. While these new approaches have provided resources and opportunities that have enabled physiological insights and taxonomic comparisons that were not previously possible, they do not provide the complete picture and continued multi‐disciplinarity is essential. This review covers the various ways in which 'omics have contributed to our understanding of adhesion by aquatic invertebrates, with new data to illustrate key points. The associated challenges are highlighted and priorities are suggested for future research.